PERUBAHAN BUDAYA HUKUM DALAM PELAKSANAAN PELAYANAN KESEHATAN SECARA DIGITAL - Amalia, Nur Bayti; Farida, Mutiara; Aszahra, Kuni Nela Rizki (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Changes in legal culture in the implementation of digital health services are triggered by several factors, including technological developments, changes in community behavior, and demands for better access and quality of health services. This also includes inadequate regulatory adaptation to digital technology trends in health services. The purpose of this study is to understand the changes in legal culture that have emerged as a result of the digitalization of health services and the extent to which the existing legal framework regulations in Indonesia are able to accommodate digital health transformation. The study in this study uses a method that is a series of activities sourced from various libraries comprehensively without collecting primary data directly in the field. The use of technology in accessing services is balanced with adequate regulations. Digital health services encourage changes from a service model that focuses on physical visits to a more integrated and personal model. Telemedicine is defined as a form of health service that uses information and communication technology that is connected to the national health information system to support health services and assist health workers in treating patients. Changes in legal culture in digital health services ensure that health technology is used safely, effectively, and ethically.Keywords: Legal Culture Change, Health Services, Digitalization.